Perilaku Konsumtif Mahasiswa Ditinjau dari Self-Regulation dan Kecerdasan Emosional - Dinda Wahyu Puspa Ningrum; Erwanto Erwanto; Mohammad Nursalim Malay (Universitas Muhammadiyah Metro, 2026)
University students are among the most vulnerable to consumptive behavior, desire-driven purchasing amplified by the constant accessibility and promotions of e-commerce platforms. Emotional intelligence and self-regulation are two psychological constructs considered crucial for inhibiting impulsive spending and directing rational consumption decisions.Â This study aimed to examine the simultaneous and partial influence of self-regulation and emotional intelligence on consumptive behavior among active university students in Lampung Province. A quantitative correlational design was employed with 222 active university students recruited through purposive sampling, consisting of students aged 18–25 years who had made at least three non-essential purchases in the past month. Data were collected using three validated psychology scales: the Consumptive Behavior Scale (Î± = .923), the Self-Regulation Scale (Î± = .920), and the Emotional Intelligence Scale (Î± = .923). Data analysis was performed using Pearson correlation and multiple regression in JASP 0.95.4. The results of the study indicate that self-regulation and emotional intelligence are both negatively correlated with consumptive behavior (R = 0.519), with a significance level of p < 0.001, and together account for 26.9% of the variance. These findings contribute to consumer psychology literature by demonstrating that self-regulation is the dominant psychological inhibitor of consumptive behavior, with practical implications for psychoeducational programs aimed at promoting healthier financial behavior among university students.